FINANCIAL EVALUATION OF AIRCRAFT ACQUISITION ALTERNATIVES: LEASE VERSUS BUY DECISION FOR GARUDA INDONESIA’S BOEING 737 MAX - Richlah Nia; Sylviana Maya Damayanti (PT. Radja Intercontinental Publishing, 2026)
This study evaluates aircraft acquisition alternatives for Garuda Indonesia’s Boeing 737 MAX procurement by comparing direct purchase, sale and leaseback, operating lease, and financial lease structures. The analysis is motivated by Garuda Indonesia’s post restructuring condition, fleet readiness constraints, aircraft redelivery obligations, and the need to renew its aging narrow body fleet. A discounted cash flow model is used to calculate Net Present Value (NPV), supported by Net Advantage to Leasing (NAL), SWOT analysis, and sensitivity analysis. The base case result shows that leasing-based alternatives provide stronger financial value, with financial lease recording the highest result among all acquisition alternatives. Direct purchase records an NPV of USD 38.569 million and is used as the benchmark. Sale and leaseback records an NPV of USD 44.041 million, operating lease records USD 47.920 million, and financial lease records the highest NPV of USD 48.047 million. Financial lease also generates the highest NAL NPV of USD 9.478 million. The sensitivity analysis indicates that financial lease remains the strongest alternative in most scenarios, although the result is sensitive to WACC, residual value, and monthly base rent assumptions.